Agency hiring in government owned and controlled corporations - Belandres, Arlene D.; Rivero, Gloria P. (2006)
Organizations, whether it is public and private, it was greatly affected by the sudden downward shift in the economy. This is the reason why government institutions especially the government and cotrolled corporations rsorted to agency hiring not just with security and janitorial services but also with clerical work in order to respond to this crisis. Agency hiring is the common term used in referring to what the Labor Code had defines as recruitment and placement. It refers to any act of canvassing, enlisting, contracting, transporting, utilizing, hiring or procuring workers, and included referrals, contract services, promising or advertising for employment, locally or abroad, whether for profit or not: Provided, that any person or entity which, in any manner, offers or promises for a fee, employment to two or more persons shall be deemed engaged in recruitment and placement. It mostly caters to janitorial, security and clerical services. the study was conducted on selected government owned and controlled corporations namely GSIS (Government Service Insurance system), DBP (Development Bank of the Philippines0, Landbank and Philippine Health Insurance Corporations (PHILHEALTH). Each agency was given 15 questionnaires were divided to as follows: seven (7) to clerical, two (2) to janitors and (6) to security guards and also 15 fifteen heads and department heads were interviewed using the guide questions. primary and secondary data were used in the study. The advent of agency hiring prompted us, researchers to undertake this study. the results of the study are presented in the order of their objectives as follows : 1) On the responsibilities of GOCC's in hiring contractual employees. GOCC's does not have any responsibilities or in any form concerning their contractual employees since, they re third party 3rd party to the contract. It is the responsibility or the custody of the agency, itself. ; 2) On whether the practice of agency hiring violates any provision of the Labor code. The Labor Code is silent as to with regards to the legality of agency hiring. Furthermore, it does not prohibit any company to stipulate the term or period or the duration of work of the employees whether it is over or lesser than six months especially it the company just would like to protect their management ideologies; 3) On the reasons why government financial institutions resort to agency hiring. GOCC's resorted to agency hiring because of cost minimization since; it is one of their primary concerns. Most of their expenses were comprised of salary and benefits. Indulging into agency hiring lessen these particular expense since, agency hired employees were paid less compared to regular employees; 4) On the reasons why contractual employees were hired to render janitorial and security services. A few belong to clerical work. They still patronize or continue to serve the agency due to they are paid above the minimum wage rate and were given higher benefits. For the case of clerical employees they continue to serve the agency with the aim that in the future they would be given a regular position; 5) On the effects of agency hiring to contractual employees. Most contractual employees admitted that theri salary, could not meet their basic needs however, they are not happy with it. They are also comfortable with their status and renders services for the reason of salary. After conducting the study the groups recommends that there should be laws formulated to safeguard the rights of contractual employee. They should also be provided with yearly physical check-up and be allowed to form unions.
[Research Paper (Mgt 299-Research Methods in Management). -- [Iloilo City : UPV-CM], February 18, 2006.